A Leftist Demonstration, on the Asian Bank of the Bosphorus, Two Decades ago - Çaya, Sinan (Advances in Social Sciences Research Journal, 2016)
This work is an attempt to analyze ―through conventional as well as ethno-methodological and phenomenological methods of Sociology― the social facts behind a youth riot on a labor-day, in Istanbul, in 1996, wherein life and property losses occurred. Key words: Riot; shanty towns; police; policeman; Istanbul.